MEASUREMENT OF RADON 86RN CONCENTRATION IN SOIL TAKEN FROM AREA SITUATED IN ANBAR GOVERNORATE BY USING THE NUCLEAR TRACK DETECTOR(CR-39) - MAZIN .H. HASSAN (مجلة جامعة الانبار للعلوم الصرفة, 2010)
This research was conducted at radon 86Rn concentration in soil by using alpha-emitters registration emitted form Radon gas in (CR-39) detector from an area situated in Anbar governorate. Conducted concentrations in soil samples were measured in (6) regions (Garma, Amertiat Al-Falluja, Saqlawia, Sacher, Habania, Falluja). The concentration values were calculated by a comparison with standard samples. The results obtained show that the higher concentrations at Radon gas in Falluja region was (356.4 Bq/m3) followed Sacher region (275 Bq/m3) and in Amertiat Al-Falluja region (269.6Bq/m3) than Habania region (198.2 Bq/m3) than Saqlawia region (146.6 Bq/m3) finally Al-Garma region (102.8 Bq/m3). We have showing that the Radon gas concentration in Falluja region is higher than the other regions.